2010
DOI: 10.2109/jcersj2.118.749
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite ceramics coating on magnesium alloy via a double layered capsule hydrothermal hot-pressing

Abstract: Hydroxyapatite (HA: Ca 10 (PO 4 ) 6 (OH) 2 ) ceramic coating on magnesium (Mg) alloy (AZ31; Mg3Al1Zn) was achieved simultaneously by using a double layered capsule hydrothermal hot-pressing (DC-HHP) method at the low temperature as low as 150°C with no special surface treatment on the surface of the Mg alloy. A mixture of calcium hydrogen phosphate dehydrate (DCPD) and calcium hydroxide (Ca(OH) 2 ) was used as a starting powder material for solidifying HA. Pull-out tests were conducted in order to obtain an es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Just a few publications were found on the topic and they were devoted to HA deposition on AZ31 Mg alloy [562] and Ti [9,563,564]. In order to create suitable hydrothermal conditions, double-layered capsules were used: the inner capsule encapsulated the deposited materials and a substrate, while the outer one was subjected to isostatic pressing under the hydrothermal conditions.…”
Section: A Double Layered Capsule Hydrothermal Hot Pressingmentioning
confidence: 99%
See 1 more Smart Citation
“…Just a few publications were found on the topic and they were devoted to HA deposition on AZ31 Mg alloy [562] and Ti [9,563,564]. In order to create suitable hydrothermal conditions, double-layered capsules were used: the inner capsule encapsulated the deposited materials and a substrate, while the outer one was subjected to isostatic pressing under the hydrothermal conditions.…”
Section: A Double Layered Capsule Hydrothermal Hot Pressingmentioning
confidence: 99%
“…In addition, it was revealed that HA remained on the surface of the Mg alloy after the pullout fracture tests. Thus, by means of this technique, HA deposits could be bonded to Mg and its alloys with good adhesive properties [562].…”
Section: A Double Layered Capsule Hydrothermal Hot Pressingmentioning
confidence: 99%
“…Biodegradable and biocompatible calcium phosphate (Ca‐P) coatings are preferred in biomedical applications because Ca‐P is a main inorganic constituent of natural bone and can speed up bone growth . However, the main issue for pure Ca‐P coatings is their brittleness, potentially leading to early failure of the bone–implant interface.…”
Section: Introductionmentioning
confidence: 99%
“…7,11 Biodegradable and biocompatible calcium phosphate (Ca-P) coatings are preferred in biomedical applications because Ca-P is a main inorganic constituent of natural bone and can speed up bone growth. 12,13 However, the main issue for pure Ca-P coatings is their brittleness, potentially leading to early failure of the bone-implant interface. Use of composite coatings can be an ideal approach to overcome this issue, and they can be formed by a combination of Ca-P as inorganic part and bioresorbable polymers as organic component.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous reports, we have proposed a HHP method for bonding HA ceramics and pure Ti, Ti alloys, Magnesium alloy, and Ti based bulk metallic glass by hydrothermal hotpressing techniques [Onoki et al, 2003a[Onoki et al, , 2003b[Onoki et al, , 2005[Onoki et al, , 2006[Onoki et al, , 2008a[Onoki et al, , 2008b[Onoki et al, 2009a[Onoki et al, , 2009b[Onoki et al, , 2010a[Onoki et al, , 2010b[Onoki et al, , 2010c[Onoki et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%